POLITIK HUKUM TERHADAP PEDAGANG KAKI LIMA DARI PERSPEKTIF UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - Suardin, Yohannes (Universitas Katolik Santo Thomas Medan, 2020)
The existence of the 1945 Constitution of the State of the Republic of Indonesia has been quite clear that it also encompasses marginal communities, one of which is street vendors, although explicitly it cannot be read. This is already apparent from one of the national goals contained in the 4th paragraph Opening of the Constitution of the Republic of the Republic which states